Draft Annual Plan (2004-05) Administration of Union Territory of Dadra and Nagar Haveli - Planning Commission (Planning Commission, 2004)
Dadra and Nagar Haveli was born on 17th December, 1779 is a result of a treaty between Portuguese and Marathas. The Marathas assigned 72 villages to Portuguese in return of their friendship and the group of the 72 villages came to be known as Dadra and Nagar Haveli. The Portuguese ruled this territory until its liberation on 2nd August, 1954. After its liberation, local body known as Free Dadra and Nagar Haveli till its merger with the Indian Union on 11th August 1961 carried out the Administration. Consequently, the Free Dadra and Nagar Haveli Administration was succeeded by formal statutory Administration headed by an Administrator.
Union Territory of Dadra and Nagar Haveli, Department of Planning and Statistics